A Postural Tremor Highly Responsive to Transcranial Cerebello-Cerebral DCS in ARCA3 - Bodranghien, Florian; Oulad Ben Taib, Nordeyn; Van Maldergem, Lionel; Manto, Mario (Frontiers in Neurology, 2017)
Background and Objectives: Cerebellar ataxias are disabling disorders which impact on the quality of life of patients. In many cases, an effective treatment is missing. Despite the increasing knowledge on the pathogenesis of cerebellar disorders including genetic aspects, there is currently a gap in the therapeutical management of cerebellar deficits. Cerebellar ataxia associated with ANO10 mutation (ARCA3) presents with a disabling cerebellar syndrome. To report a patient with a marked postural tremor responding to transcranial cerebello-cerebral direct current stimulation (tCCDCS). Methods: We applied tCCDCS using anodal stimulation over the cerebellum with a return electrode on the contralateral motor cortex. We performed a clinical rating, accelerometry studies and recordings of voluntary movements at baseline, after sham and after active tCCDCS. Results: A dramatic response of postural tremor was observed after tCCDCS, with a major drop of the power spectral density (PSD) to 26.12 % of basal values. Discussion: The postural tremor of cerebellar ataxia associated with ANO10 mutation was highly responsive to tCCDCS in our patient. This case illustrates that tCCDCS is a novel therapeutic option in the treatment of cerebellar deficits and might represent a promising tool to reduce tremor in ARCA3.